O Pagamento por Serviços Ambientais nas Áreas de Preservação Permanente da Bacia do Ribeirão da Confusão no Município de Rancharia - SP: um estudo sobre a viabilidade econômica da implantação - JARDIM, A. M. (2016)
Brazil is considered one of the countries with the greatest number of environmental legislation in the world, ingroducing as Governmental strategy the use of command-and-control standards in the conservation of areas of permanent preservation and legal reserve located in rural properties. However, the so-called environmental punishment rules (command and control) have been showing an ineffective result, discouraging rural producers in the care of their environmental areas because the reforestation (planting, cleaning the land, fencing in the area, pest control, seedlings) presents itself very costly for producers. Some economic instruments, however, have been being used in the preservation of resources, in particular the payment for environmental services (PSA), used by many countries in Latin America and in Brazil, this payment model is gaining economic strength. The payment for environmental services is presented as a Prized Punishment, one that does something positive for the environment, should be awarded a prize or reward for the option of keeping the forest standing, taking care and pricing the marginalised services by the market. The work had as main objective to present the importance of payment for environmental services in areas of permanent preservation (APP) in an area located in the basin of the Confusão stream within Rancharia- SP city. At first, the bibliographic survey was about the topic and from seized theories and concepts raised, mapping were held as: arboreal vegetation, water resources and permanent preservation areas. Secondly, we conducted a survey of data through documental research (satellite images and data from the IBGE) in Rancharia city, focusing on the properties located on the banks of the Confusão basil. The hypothesis adopted in this work is that the payment for environmental services in the city of Rancharia is viable and this will facilitate the awareness of farmers in conservation of natural resources within the municipality. The research here adopted, was based on a qualitative research, using the bibliographical and documentary research and techniques of direct intensive observation. It was concluded that the implementation of the payment for environmental services in the areas of permanent preservation located in the basin of the Confusão, would contribute to the formation of public policy focused on the management of natural resources located in the city of Rancharia, in order to restore these forests, due to the multitude of ecosystem services that they provide to all collective. However, the results of the survey showed that it will only be possible through the installation of public policy adhered by municipal bodies.